Ответы и объяснения

2012-10-09T22:10:22+04:00

(5 - 3x) / 7 = 5 + x

5 - 3х = 7 * (5 + x)

5 - 3x = 35 + 7x

-3x - 7x = 35 - 5

-10x = 30 | : (-10)

x = -3

 

(x - 4) / 5 - (x + 2) / 2 = -3 / 10

(2 * (x - 4) - 5 * (x + 2) + 3) / 10 = 0  | * 10

2x - 8 - 5x - 10 + 3 = 0

-3x = 15  | : (-3)

x = -5

2012-10-09T22:15:03+04:00

(5-3х)/7=5+х,(5-3х)-делимое,

5-3х=(5+х)*7

5-3х=35+7х

-3х-7х=35-5

-10х=30

х=30/(-10)

х=-3

(х-4)/5-(х+2)/2=-3/10,представить ввиде дроби,кпривести к знаменателю 10

(х-4)/5*2-(х+2)2)*5=-3/10

2х-8-5х-10=-3

-3х-18=-3

-3х=-3+18

-3х=15

х=-5

проверим 2*(-5)-8-5*(-5)-10=-3

               -10-8+25-10=-3

                -28+25=-3

                   -3=-3